Simulasi Pertolongan Pertama pada Kecelakaan dalam Meningkatkan First Aid Awareness pada Siswa SMAN 5 Tegal - Dimas Prastia; Rizky Meisilvia; Febyana Wulandari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity aims to improve the First Aid Awareness of students at SMAN 5 Tegal through health education and first aid simulation for accident management. The background of this program is based on the high potential for mild to moderate emergency incidents in the school environment, such as fainting, open wounds, nosebleeds, choking, and seizures, as well as the limited knowledge and practical skills of students in providing appropriate initial assistance. The implementation method consisted of three stages: preparation, delivery of health education using presentations and demonstrations, and hands-on simulation, followed by evaluation through knowledge assessment and skills observation. The participants were 54 students representing three grade levels. The expected outcomes of this activity include an improvement in students’ conceptual understanding and practical ability to perform first aid quickly, correctly, and safely before professional medical help arrives. In addition, this program is expected to foster emergency responsiveness, increase students’ confidence in handling accident situations at school, and contribute to the development of a safer and more prepared school environment. The outputs of this activity include increased knowledge and skill scores, documented implementation, and publication of a community service article in a SINTA-indexed journal.